Florileges 87 d'Art Contemporain. - Salle Jacques Brel, Faches-Thumesnil (Faches-Thumesnil : Association Vu d'Ici, 1987)
Arickx, Lydie ; Aubert, Michel ; Benedito, Concha ; Cerredo, Fabian ; Christoforou, John ; Franta ; Gillet, Roger-Edgar ; Jonneskindt, Philippe ; Leger, Silviane ; Lindström, Bengt ; Maryan ; Pelayo, Orlando ; Rocher, Maurice ; Roulland, Jean ; Subira-Puig, José
Florileges 87 d'Art Contemporain, Salle Jacques Brel, Faches-Thumesnil, du vendredi 5 Juin au jeudi 25 Juin 1987
boek